Psychopathology, Body Image and Quality of Life in Female Children and Adolescents With Anorexia Nervosa: A Pilot Study on the Acceptability of a Pilates Program - Martínez-Sánchez, Sofía M.; Martínez-García, Concha; Martínez-García, Tomás E.; Munguía-Izquierdo, Diego (Frontiers in Psychiatry, 2020)
Background: Anorexia nervosa (AN) is a psychiatric illness that without early effective treatment becomes chronic with high physical, psychological and social morbidity and high mortality. Pilates exercises can improve quality of life and increase body awareness in different clinical and healthy populations. The aim of this pilot study was to examine the acceptability of a Pilates program in a sample of female children and adolescents with AN by evaluating the psychopathological status, alterations in the perception of body image and health-related quality of life after 10 weeks. Methods: A total of 12 female patients (age: 14.6  1.7 years) completed the 10-week Pilates program. Psychopathology (EDI-3), body image disturbance (CDRS) and quality of life (KIDSCREEN-27) were evaluated before and after the intervention. A satisfaction questionnaire was also provided. Results: Regarding psychopathology, although there were standardized reductions in 7 parameters of those that form EDI-3, none of them reached significance. In relation to body image, significant, moderately standardized and substantial decreases were observed in the body dissatisfaction (p = .046, Cohen's d = -0.69). There were significant, large standardized and substantial increases in physical well-being (p = .008, Cohen's d = 1.37) and significant, moderately standardized and substantial decreases in autonomy and parent relation (p = .021, Cohen's d = -0.60). Satisfaction data was positive. Conclusion: A Pilates program could help to improve perceived health outcomes by decreasing body dissatisfaction and increasing physical well-being in female children and adolescents with AN, so Pilates seems to be a beneficial complementary treatment in children and adolescents with AN. These findings from our pilot study are encouraging for future research with a substantially larger sample size, representing the first phase of a longer process.